Peningkatan Pengetahuan Tentang Manfaat Asi Eksklusif Melalui Kegiatan Penyuluhan Kesehatan Di Posyandu Tebing Tinggi Wilayah Kerja Puskesmas Abeli Sulawesi Tenggara - Adelia Putri Rahayu; Sartiah Yusran; I Putu Sudayasa; Alfiandi; Elsa Putriani Gunawas; Faskal Othneil Pratama Kaperek; Imran; Intan Anugrah Pratiwi; Iyan Megawati Adiwijaya; Suriani (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2026)
Breast milk is the best food for babies, especially during the first six months of life. Exclusive breastfeeding has been proven to benefit babies' growth, development, and immunity, as well as providing health benefits for mothers. However, exclusive breastfeeding in Indonesia has not yet met the national target. This is influenced by various factors, primarily mothers' knowledge. The purpose of this activity is to increase the understanding of pregnant and breastfeeding mothers about the benefits of exclusive breastfeeding, the correct methods and techniques of breastfeeding, and the importance of preparing oneself during pregnancy. The target audience for this activity is pregnant and breastfeeding mothers, with 15 participants. It is held at the Tebing Tinggi Health Center in the Abeli Public Health Center working area. The counseling method involved showing educational videos, delivering material interactively, holding discussions, and conducting question and answer sessions. The results of the activity showed enthusiasm and active participation from the participants during the counseling session. Participants were able to understand the definition of exclusive breastfeeding, the benefits of breast milk for babies and mothers, the appropriate time and method of breastfeeding, and the factors that influence the success of exclusive breastfeeding. This educational activity effectively increased mothers' knowledge and awareness of the importance of exclusive breastfeeding. It is hoped that ongoing education and support from families, health workers, and Posyandu cadres can improve the success of exclusive breastfeeding practices in the community.